Solar thermal energy trapping mechanisms in practice - Gilani, S.I.-H. (Springer Verlag, 2019)
Sun is the only source of energy to the earth on which the whole global activities are dependent. Solar energy is the starting point for natural, chemical and biological processes in this world in the early days and it is the most environmental-friendly form of energy. It can be used in many ways and it is suitable for many sorts of solar/chemical systems. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2019.